SISTEM KEAMANAN RUMAH TERINTEGRASI DENGAN SENSOR REED SWITCH DAN PIR MENGGUNAKAN PLATFORM IOT - Bagus Pranata, Ramadani; Oktari Aulia, Regita; Dwisaputra, Indra; Putra Maulana, Ade (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2025)
Abstract is arranged in one paragraph, single line spacing with Times New Criminal acts, particularly home burglaries—whether in occupied or unoccupied houses—are still frequently reported. This pushes homeowners to be more vigilant in securing their properties. Despite technological advancements, especially in the field of the Internet of Things (IoT), existing home security systems are still not fully effective. This research proposes a home security system called HERO (Home Reliability Operations) based on IoT, which operates automatically and in real-time. The system uses a PIR sensor to detect movement, an ESP32-CAM OV2640 for visual monitoring, and a buzzer as an alarm alert. To secure entry points, magnetic switch sensors and solenoid door locks are installed on doors and windows. All components are controlled by a NodeMCU ESP32 as the central processor and connectivity hub, and the system is integrated with the Blynk platform for remote monitoring and control via an Android application. This system is expected to improve home security by enabling early detection of suspicious activity and providing real-time alerts to homeowners.